Over a million students use our free study notes to help them with their homework
rewrite as y = 4x^5 - 5x^(-2)
dy/dx = 20x^4 + 10x^(-3)
integral of y = 4x^6 / 6 + 5x^(-1) / 1 + c
simplify: 2/3 x^6 + 5/x
i) There first step is to acknowledge the need for both product rule (d(uv)/dx=v.du/dx+u.dv/dx) and chain rule (dz/dx=dz/dy*dy/dx). Here, u=x^3 and v=ln(2x). Therefore, du/dx=3x^2 which is a standard diff...
For a quotient f(x) = u(x)/v(x), the derivative is f'(x) = (vu'(x) - uv'(x))/v(x)2. Applying this to the given function, we find u(x) = x+3 and v(x) = 2x-5. So, u'(x) = 1 and v'(x) = 2...
u=x2 + 3
du/dx=2x
dx=du/2x
2x/(x2+3) dx becomes (2x/u) * (du/2x)
the 2x terms cancel out giving 1/u du
this integrates to ln(u)+c becoming ln(xAnswered by Tom S. • Maths tutor12554 Views
First what we need to do is we need to think of what the question is asking us to find. In this case it is dy/dx but what is this. This is the rate of change of y with respect to x. For understanding pur...
←
381
382
383
384
385
→
Internet Safety
Payment Security
Cyber
Essentials